Fate of perfluoroalkyl substances within a small stream food web affected by sewage effluent. (1st May 2018) - Cerveny, Daniel; Grabic, Roman; Fedorova, Ganna; Grabicova, Katerina; Turek, Jan; Zlabek, Vladimir; Randak, Tomas
Abstract: The fate of fourteen target perfluoroalkyl substances (PFASs) are described within a small stream affected by a sewage treatment plant (STP) effluent. Concentrations of target PFASs in samples of water, benthic macroinvertebrates and brown trout ( Salmo trutta ) are presented. Two hundred brown trout individuals originating from clean sites within the same stream were tagged and stocked into an experimental site affected by the STP's effluent. As a passive sampling approach, polar organic chemical integrative samplers (POCIS) were deployed in the water to reveal the water-macroinvertebrates-fish biotransformation processes of PFASs. Bioconcentration/bioaccumulation of target compounds was monitored one, three, and six months after stocking. Twelve of the fourteen target PFASs were found in concentration above the LOQ in at least one of the studied matrices. The compound pattern varied significantly between both the studied species and water samples. Concerning the accumulation of PFASs in fish, the highest concentrations were found in the liver of individuals sampled after three months of exposure. These concentrations rapidly decreased after six months although the water concentrations were slightly increasing during experiment. Graphical abstract: Image 1 Highlights: Local STPs represent significant source of PFASs in the aquatic environments. Organisms at different trophic positions express different compound pattern in body. PFASs content decreased in benthic organisms according to the distance from STP. Adaptation on polluted locality was registered in fish after six months of exposure.